Real World Adobe InDesign CS3 - Kvern, Olav Martin; Blatner, David (Peachpit Press, 2008)
A guide to the desktop publishing and page layout program covers manipulation of text and graphics, adding transparency effects, optimizing the PDF workflow, and customizing with AppleScript, JavaScript, and Visual Basic.